The Effectiveness Of Electronic Parking By The Samarinda City Transportation Department (Case Study: KH. Khalid Street, Pasar Pagi) - Muna Warah; Friska Prastya Harlis (Universitas Negeri Gorontalo, 2026)
The concept of a smart city refers to an urban planning approach that utilizes technological advancements to improve the quality of public services, transparency, and governmental accountability. The implementation of this concept is expected to effectively and efficiently address various urban problems. Samarinda City, as one of the cities adopting the smart city concept, implements it through various service innovations, one of which is the electronic parking system (E-Parking) managed by the Samarinda City Transportation Agency. This study aims to analyze the effectiveness of the implementation of the electronic parking (E-Parking) system, with a case study on KH. Khalid Street, Pasar Pagi, which has a high level of community activity. This research uses a qualitative approach with a descriptive research type. Data collection techniques include observation, interviews, and documentation. Data analysis employs the policy effectiveness theory proposed by Riant Nugroho, which includes indicators such as appropriate policy, appropriate implementers, appropriate targets, appropriate environment, and appropriate process. The results show that, normatively, the E-Parking policy has been implemented and has contributed to increasing local revenue as well as supporting smart city principles. However, in practice, several obstacles are still found, such as the dominance of cash transactions, limited availability of EDC devices, and suboptimal monitoring and supervision. Other inhibiting factors include limited human resources, community habits, and lack of consistency among field implementers. Therefore, it can be concluded that the effectiveness of E-Parking implementation has not yet been optimal.